Is it a financial or a management crisis? Evolution of the health sector from the perspective of territorial entities (2016)
The problems of the health sector in the territorial entities have mainlybeen seen from a financial perspective. Thus, efficiency problems havebeen treated with fiscal and financial measures. This article presents the financialsituation of the health sector from the territorial entities perspective,which includes the study of regulation and the main financial factsbetween 2010 and 2014. In the last years local health funds have had a financialsurplus, which suggests that public policy should transcend the financialissue and concentrate on strengthening institutional and managementtools to improve health results.